Abundance, Diversity, and Distribution of Fish Larvae in The Bali Strait - Satyawan, Noar Muda; Suhery, Noveldesra; Kelana, Perdana Putra; Triyono, Heri; Prasetyo, Ganang Dwi; Prayitno, Muhamad Riyono Edi; Tiku, Mathius (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2025)
Larva represents the initial phase of a fish’s life after hatching from the egg. Studies on fish larvae aim to provide seasonal information, as well as identify spawning and nursery areas, especially economically important fish species, to support the sustainability of fishery resources. This study aimed to gather information on the abundance, diversity, and distribution of fish larvae in the waters of the Bali Strait. Sampling was carried out from August to November 2024, using a trawl net at five observation stations. The larval samples were preserved with 4% formalin and subsequently identified and counted using a microscope at the Capture Fisheries Laboratory of Marine and Fisheries Polytechnic of Jembrana. This study found 22 families of fish larvae, with abundance ranging from 38 to 433 individuals per 1000 m3. Spatially, the highest abundance was recorded at the Perancak station, followed by Tuwed, Sumbersari, Cupel, and Jimbaran. Temporarily, fish larvae with high abundance were found from September to November. The larval composition was dominated by the families Clupeidae, Gobiidae, Bramidae, and Carangidae. Shannon-Wiener Index (H') of fish larvae ranged from 0.64 to 2.18, indicating that the level of diversity and stability of the community was at a low–moderate level. The highest diversity was found at Tuwed station. The distribution of fish larvae is influenced by oceanographic characteristics, fish behavior, and the availability of natural food sources, such as plankton.